Clinical and genetic risk factors associated with neonatal severe hyperbilirubinemia: a case–control study based on the China Neonatal Genomes Project - Wang, Xiao; Xiao, Tiantian; Wang, Jin; Wu, Bingbing; Wang, Huijun; Lu, Yulan; Wang, Yaqiong; Chen, Bin; Hu, Liyuan; Cao, Yun; Zhang, Rong; Cheng, Guoqiang; et al. (Frontiers in Genetics, 2024)
Objective To investigate the clinical and genetic risk factors associated with neonatal severe unconjugated hyperbilirubinemia.This was a retrospective, 1:1 matched, case-control study. We included 614 neonates diagnosed with severe unconjugated hyperbilirubinemia (serum total bilirubin level ≥ 425 μmol/L or serum total bilirubin concentration that met exchange transfusion criteria), from the China Neonatal Genomes Project in Children's Hospital of Fudan University. Clinical exome sequencing data were analyzed using a data analysis pipeline of Children's Hospital of Fudan University. The factors associated with severe unconjugated hyperbilirubinemia were assessed using univariable and multivariable logistic regression analyses. Interaction analyses were examined between clinical and genetic risk factors.Results ABO/Rh incompatibility hemolysis (OR 3.36, 95% CI 2.32 to 4.86), extravascular hemorrhage (OR 2.95, 95% CI 2.24 to 3.89), weight loss (OR 5.46, 95% CI 2.88 to 10.36), exclusive breastmilk feeding (OR 3.56, 95% CI 2.71 to 4.68), and the homozygous mutant of UGT1A1 211G>A (OR 2.35, 95% CI 1.54 to 3.59) were all identified as factors significantly associated with severe unconjugated hyperbilirubinemia. The presence of UGT1A1 211G>A mildly increased the risk of severe unconjugated hyperbilirubinemia caused by ABO/Rh incompatibility hemolysis (OR 3.98, 95% CI 2.19 to 7.23), although the effect is not statistically significant.